Wspólny udział małżonków w Eucharystii - Migut, Bogusław (Studia Pastoralne, 2009)
This article refers first to the Church’s recent teaching on the Eucharist and the sacrament of matrimony, and second shows a close relation between the two sacraments and the principle of participation of spouses in the Eucharist. The principles issue from the very essence of the Holy Mass and its structure. They are also dictated by the sacramental bond that ties spouses. The bond between the Eucharist and matrimony issues from their reference to the mystery of Christ. Both the sacraments are signs of Christ’s mystery; the Eucharist makes the whole of Christ’s mystery present, and matrimony is a sign of Christ’s mystery as a mystery of the nuptials, that is the revelation of the Father’s love towards the Church and of the Church’s voluntary resignation to the Father in Jesus Christ. It is a sign of Christ’s mystery, interpreted as a sign of the unity of God and people, and first of all a sign of Christ’s love towards the Church. Marriage as a covenant between a manand a woman in God is revived, or is constantly reborn, by the spouses’ participation in the sacrament of the altar. Moreover, the bond between matrimony and the Eucharist is inscribed in the bond between the Church and the Eucharist.